Photogrammetry Experiment at Fagradalsfjall, Iceland ... - Ukstins, Ingrid; Hamilton, Christopher W.; Carr, Brett (University of Arizona Research Data Repository, 2024)
This dataset contains products from unoccupied aircraft system (UAS) surveys conducted at Fagradalsfjall volcano, Iceland, in May 2024. A survey from May 27, 2024, is located north of Litli-Hrútur and covers the 2023 eruption vent and surrounding area. Two surveys from May 29, 2024, are located at the eastern end of Meradalir valley and includes parts of lava flows emplaced during eruptions in 2021, 2022, and 2023. These two surveys have the same spatial extent. One was flown at 55 meters above ground level (AGL) and the other at 111 m AGL. The purpose of these two flights was to acquire an image dataset at multiple resolutions for simulated virtual surveys through the volume above the target using machine learning to dynamically inform flight planning.The data included for each survey consists of a digital elevation model (DEM), orthomosaic, point cloud, processing report, and original images from the UAS. All data products are presented in the ISN2016 (EPSG:8088) coordinate reference system. The photo ...